Gente que planta os pés no chão: disputas territoriais no Parque Estadual da Mata Seca - Júlia Veloso dos Santos (2018)
The Dry Forest State Park, located in the municipality of Manga/MG, on the left bank of the São Francisco River, is a scenario of territorial disputes between the traditional community of Pau de Légua, agribusiness rural enterprises and environmental public agentes. With different views and rationalities about the use and appropriation of land and natural resources, the social actors in dispute represent different property disciplines that collide with each other, causing an obstacle to land regularization. The place is traditionally occupied by the traditional community of Pau de Légua, which first went through a time of rupture with the expropriation of its territory by the implementation of developmental policies in the region and afterwards, went through a moment of intensification of the crisis with the implementation of compensatory environmental policies to the Irrigated Perimeter of Jaíba. Through a qualitative approach, using the ethnographic method, the present study aimed to understand the environmental conflict that was established in the Dry Forest State Park, as well as its originsand unfolding. The aim was to identify the dynamics of the conflict by analyzing the social actors in dispute and their different territorialities, comprehending historically the economic, land and socio-environmental processes that underlie the environmental conflict under analysis.